PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS ANDROID UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN KIMIA - Nordiana, Lia; Mansur, Hamsi; Sari, Nina Permata (Akademika : Jurnal Teknologi Pendidikan, 2025)
This research aims to: (1) design and create Android-based Augmented Reality learning media for chemistry subjects, (2) ascertain the suitability of the developed media, and (3) assess its effectiveness in enhancing students' learning enthusiasm. This study employs Research and Development (R&D) methodology, utilizing the ADDIE model (analysis, design, development, implementation, and evaluation). The limited trial subjects are students from class XI A at SMA Negeri 1 Lampihong. Data collection techniques include: observation, validation from media experts, material experts, and learning interest questionnaires. Data analysis was performed descriptively both qualitatively and quantitatively, employing Likert Scale calculations and N-Gain analysis. The research findings received a score of 66, with a percentage of 94.28% from media experts, and a score of 54, with a percentage of 90% from material experts. Meanwhile, the N-gain calculation results yielded an average value of 0.57, which falls into the